A solution for reducing the degree of polynomial composition functions using Faà di Bruno’s formula and Fourier transform - Ahani, Elshan; Ahani, Ali (Springer Science and Business Media LLC, 2023)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Faà di Bruno's formula; Fourier and Fourier-Stieltjes transforms and other transforms of Fourier type; Fourier transform; Bell's polynomial; Nonlinear ordinary differential equations and systems; degree reduction; Transformation and reduction of ordinary differential equations and systems, normal forms